Penilaian Tingkat Pencemaran Air S. Bengawan Solo Dengan Menggunakan Indeks Kimia-Fisika - Armaita Sutriati (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2012)
River water quality at various places in Indonesia continues to decline due to pollution by domestic, industrial, and agriculture waste. The Pollutant Index of Solo River is showing conditions from “lightly polluted” to “medium polluted”. These conditions cause the river water quality to be no longer appropriate to its designation. This study aims to assess the level of water pollution of the Solo River using the chemical-physical index. By knowing the level of water pollution, the water resources management can prioritize certain sections for improved water quality, so that it can be developed as a source of raw water for a variety of purposes. The chemical-physical index can be limited to one data measurement (grab sampling data), so its use may be another alternative to rapid determination of water pollution level (WPL). The WPL in the Solo River is “very lightly polluted” to “lightly polluted” during the rainy season, but during the dry season varies greatly. The WPL of the Solo River from upstream to downstream in the period 1995 was identified from “lightly polluted” to “critically polluted” and from, “lightly polluted” to “very heavy polluted” in the period 2002-2011. Decline in water quality had significantly increased as was observed by the rising WPL value in the upstream segment during the period 2006 to 2011.